Risk factors for overuse shoulder injuries among male professional handball players - Clarsen, B.; Bahr, R.; Andersson, S.; Kristensen, R. M.; Myklebust, G. (British Journal of Sports Medicine, 2014)
Background: Overuse shoulder injuries are common among professional male handball players. However, little is known about risk factors for the development of injury. Objective: To determine whether rotator cuff strength, glenohumeral joint range of motion and scapular stability are associated with the presence of overuse shoulder problems among elite male handball players. Design: Prospective cohort study.Setting The Norwegian professional handball league for men (Postenliga). Participants A total of 206 professional players were tested prior to the 2011-12 season and followed prospectively over the course of the season (30 weeks). During this time, shoulder problems were registered bi-weekly using the Oslo Sports Trauma Research Center Overuse Injury Questionnaire. Sufficient data was collected from 162 players to be able to be included in risk-factor analyses. Risk factor assessment: Risk factor measures included: (1) Glenohumeral internal and external rotation range using a digital inclinometer; (2) isometric internal rotation, external rotation and abduction strength using a hand-held dynamometer, and (3) assessment of scapular control, using a validated subjective protocol. Main outcome measurements: A cumulative severity score was calculated for each player based on their questionnaire responses. The score reflects the degree to which they experienced shoulder pain throughout the season, as well as reductions in handball participation and performance due to shoulder problems. Results: The average prevalence of shoulder problems throughout the season was 28% (95% CI: 25-31%). A significant associations was found between obvious scapular dyskinesis and shoulder problems (OR 11.6, 95% CI 2.0-68.4, P<.05). Players with shoulder problems also had reduced Glenohumeral total rotational motion (mean difference 9°, P<.05). No significant associations were identified between isometric strength and shoulder problems. Conclusions: The prevalence of overuse shoulder problems is high among male professional handball players. This study provides important information which may help to guide the development of prevention programs.